Ответы и объяснения

  • Участник Знаний
2013-05-11T06:18:21+00:00

2cosx+cos2x=2sinx

2cosx+(2cos^2x-1)-2sinx=0

2cosx+2cos^2x-(sin^2x+cos^2x)-2sinx=0

2cosx+2cos^2x-sin^2x-cos^2x-2sinx=0
cos^2x+2cosx-sin^2x-2sinx=0

Произведём группировку

cos^2x-sin^2x+2cosx-2sinx=0

(cosx+sinx)(cosx-sinx)+2(cosx-sinx)=0

выносим общий множ. за скобки

(cosx-sinx)(cosx+sinx+2)=0

решаем по отдельности каждое ур-ие

 

1) cosx-sinx=0   /:cosx≠0

1-tgx=0

tgx=1

x=pi/4+pik, k ∈Z

 

2) cosx+sinx= - 2

√2(1/√2*cosx+1/√2*sinx)= - 2

sin(pi/4)cosx+cos(pi/4)*sinx= -2/√2

sin(pi/4+x)=-√2

-√2=1,41

нет реш. , т.к. x∈[-1;1]

 

ОТВЕТ:

pi/4+pik, k ∈Z